Proton beam therapy for recurrent ovarian carcinoma: A case report. Issue 9 (22nd July 2019) - Kino, Tamina; Ando, Noriko; Ogawara, Yuki; Shigeta, Hiroyuki
Abstract: The efficacy and feasibility of proton beam therapy (PBT) for recurrent ovarian carcinoma had not been determined. Here we presented a case of recurrent ovarian carcinoma that was successfully treated with PBT. A 48‐year‐old woman who was diagnosed as left ovarian clear cell carcinoma underwent surgery without removal of two tumors. After achieving complete remission with postoperative chemotherapy, a recurrent tumor was found in the sigmoid colon, for which a colostomy was performed. Because second‐line chemotherapy was not effective, PBT was selected; there were no complications, except for a transient low‐grade fever. After 1 year of PBT, the tumor completely disappeared and the patient had been disease‐free for over 8 years. PBT may be an effective and less invasive treatment modality for recurrent ovarian carcinoma.